Extraction of Pectin from Pomegranate Peel - Ferda Sarı; Tuğçe Birlik (Turkish Journal of Agriculture: Food Science and Technology)
In this study, pectin was extracted by acid extraction method from pomegranate peel. The temperature, time and particle size which affected pectin yield were optimized using response surface method. As a result of optimization, optimum conditions for pectin extraction from pomegranate peel were determined as 468-568 µm for particle size, 82°C for temperature and 47,5 minutes for extraction time. After the extraction at optimum conditions pectin yield was found to be 25,96%. In addition, pectin that was produced had equivalent weight of 488,01 mg, methoxyl content of 5,74%, the degree of esterification of 47,43%and anhydrogalacturonic acid content of 68,64%. The results showed that the obtained pectin was low methoxyl pectin.